The Impact of Celebrity Endorsement, Product Quality, and Brand Image on Purchasing Decisions and Customer Satisfaction of MS Glow Products in Pekanbaru City: A Formal Analysis - Rima Noviani; Aida Nursanti; Henni Noviasari; Prima Andreas Siregar (West Science Interdisciplinary Studies, 2023)
This study aims to determine how much influence celebrity endorsers, product quality and brand image have on purchasing decisions and customer satisfaction for MS Glow products in Pekanbaru city. The population of this study are all consumers who have bought and used ms glow products. This study used 147 respondents with non-probability sampling technique with purposive sampling method. This research analysis method uses path analysis with data processing using SPSS (Statistical Program Society Science) version 23 for windows. The results of this study indicate that (1) Celebrity endorser has a positive and significant effect on purchasing decisions; (2) Product quality has a positive and significant effect on purchasing decisions; (3) Brand image has a positive and significant effect on purchasing decisions; (4) Purchasing decisions have a positive and significant effect on customer satisfaction; (5) Celebrity endorser has a positive and significant effect on customer satisfaction through purchasing decisions; (6) Product quality has a positive and significant effect on customer satisfaction through purchasing decisions; (7) Brand image has a positive and significant effect on customer satisfaction through purchasing decisions.